If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -7y = -25 Solving 3 + -7y = -25 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -7y = -25 + -3 Combine like terms: 3 + -3 = 0 0 + -7y = -25 + -3 -7y = -25 + -3 Combine like terms: -25 + -3 = -28 -7y = -28 Divide each side by '-7'. y = 4 Simplifying y = 4
| 13(z+4)-4(z-1)=4(z-2)+4(z-3) | | 5x-8+3x+20=180 | | -12v-8-16v=6v-4(v+2) | | D=3-6 | | 9x+50=12x+25 | | 5(3x+1)-5x=-5(x+9)-10 | | 5+2AB=C | | 9x+80=12x+25 | | -10x=-5x | | 5(3x+1)-5=-5(x+9)-10 | | 15x-142=9x-94 | | 4=sec^2x | | 8y(-11)=6y+23 | | 2-7k=-4y+20 | | -3x+9=-2x+6 | | -7c+4-1c=-2(1c+3) | | 19x+121=12x+72 | | -12m+4+2m+1= | | 5+17x+9= | | -8x=-5x | | 12x=4(12-x) | | 20=3-2(x) | | x^3=-48 | | -12+4+2m+1= | | f(x+5)=6(x+5)-8 | | -14x-83=-8x-47 | | x-(3-x+1)=#-6 | | 3x+21=2x+13 | | f(x+5)=6x-8 | | 2(n+.3333333333333)=1.666666666666n+1+.5n-.33333333333 | | 4(x-2)=2(x-4)+2 | | 3-7y+4=2y+11-7y |